Australian men's experiences of leave provisions and workplace support following pregnancy loss or neonatal death. Issue 4 (8th August 2022) - Obst, Kate Louise; Due, Clemence; Oxlad, Melissa; Middleton, Philippa
ABSTRACT: This research note reports survey responses of Australian men ( N  = 220) gathered as part of a larger study exploring men's grief following pregnancy loss and neonatal death. We explore the types of workplace leave offered to men and how men perceived leave and support provided by their employers. Almost all men (91%) informed their workplace of their loss, and 74% were offered some form of leave. The most common types of leave offered were compassionate/bereavement leave, and sick/carers leave. Supports included Employee Assistance Programs, referral to counselling, and flexible working arrangements. Open-ended responses highlighted five themes: Emotional toll of returning to work, Need to be with and support partner, Recognition and understanding, Helpful distraction, and Pressure to return. Not all men wished to take extended (or any) paid leave following pregnancy loss or neonatal death, though they believed leave should be available. It is essential that employers recognise men's bereavement following pregnancy loss and neonatal death, and that healthcare professionals support men's decisions about work.